THE CONTRIBUTION OF ASSISTANT PHARMACISTS TO THE EXPANSION OF PHARMACY SERVICES IN COMMUNITY SETTINGS - Abdullah Ayad Aldhafeeri , Abdullah Saud Radi Al Dhafiri, Nasser Mansour Hashr Almutairi, Ajlan Muttalib Al Shammari, Rasheed Ghanam Aldhafeeri, Abdullrahman Molfi Aldhafeeri (Chelonian Research Foundation, 2022)
Background: The role of pharmacists has been expanding beyond traditional dispensing to include more clinical and patient-centered services. Assistant pharmacists play a crucial role in supporting this expansion, but their contributions have not been well-studied. Objective: To investigate the contribution of assistant pharmacists to the expansion of pharmacy services in community settings. Methods: A mixed-methods study was conducted, including a cross-sectional survey of 150 community pharmacies and semi-structured interviews with 20 assistant pharmacists. The survey assessed the types of services provided, the involvement of assistant pharmacists, and perceived barriers and facilitators to service expansion. Interviews explored the experiences and perceptions of assistant pharmacists regarding their roles and contributions. Results: Assistant pharmacists were involved in delivering a wide range of services, including medication therapy management (90%), immunizations (75%), health screenings (68%), and patient education (95%). They played key roles in supporting pharmacists, managing workflow, and interacting with patients. Barriers to service expansion included time constraints, lack of reimbursement, and limited staff. Facilitators included supportive management, training opportunities, and technology. Conclusion: Assistant pharmacists make significant contributions to the expansion of pharmacy services in community settings by supporting pharmacists, managing operations, and engaging with patients. Strategies to optimize their roles and address barriers are needed to further advance pharmacy practice and improve patient care.